Diffusion tensor imaging of the sciatic nerve as a surrogate marker for nerve functionality of the upper and lower limb in patients with diabetes and prediabetes - Jende, Johann; Kender, Zoltán; Mooshage, Christoph; Gröner, Jan; Alvarez-Ramos, Lucia; Hayes, Jennifer; Jürchott, Alexander; Hahn, Artur; Heiland, Sabine; Nawroth, Peter Paul; Bendszus, Martin; Kopf, Stefan; et al. (Frontiers in neuroscience, 2021)
Background Nerve damage in diabetic neuropathy (DN) is assumed to begin in the distal legs with a subsequent progression to hands and arms at later stages. In contrast, recent studies have found that lower limb nerve lesions in DN predominate at the proximal sciatic nerve and that, in the upper limb, nerve functions can be impaired at early stages of DN. Materials and Methods In this prospective, single-center cross-sectional study, participants underwent diffusion-weighted 3 Tesla magnetic resonance neurography in order to calculate the sciatic nerve’s fractional anisotropy (FA), a surrogate parameter for structural nerve integrity. Results were correlated with clinical and electrophysiological assessments of the lower limb and an examination of hand function derived from the Purdue Pegboard Test. Results Overall, 71 patients with diabetes, 11 patients with prediabetes and 25 age-matched control subjects took part in this study. In patients with diabetes, the sciatic nerve’s FA showed positive correlations with tibial and peroneal nerve conduction velocities (r=0.62; p<0.0001 and r=0.56; p<0.0001, respectively), and tibial and peroneal nerve compound motor action potentials (r=0.62; p<0.0001 and r=0.63; p<0.0001, respectively). Moreover, the sciatic nerve’s FA was correlated with the Pegboard Test results in patients with diabetes (r=0.52; p<0.0001), prediabetes (r=0.76; p<0.0001) and in controls (r=0.79; p=0.007). Conclusion This study is the first to show that the sciatic nerve’s FA is a surrogate marker for functional and electrophysiological parameters of both upper and lower limbs in patients with diabetes and prediabetes, suggesting that nerve damage in these patients is not restricted to the level of the symptomatic limbs but rather affects the entire peripheral nervous system.